Analisis Penerapan Isak 35 Tentang Penyajian Laporan Keuangan Entitas Berorientasi Nirlaba (Studi Kasus Pada Yayasan Perguruan Darul Aman Kota Medan) - Tessa Anggraini; Muhammad Yafiz; Rahmat Daim Harahap (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2025)
This study aims to apply the ISAK 35 concept regarding the Presentation of Financial Statements of Non-Profit-Oriented Entities at the Darul Aman College Foundation, Medan City. The concept of ISAK 35 is to allow non-profit-oriented entities to adjust the descriptions used for several items contained in the financial statements and the financial statements themselves include statements of financial position, statements of comprehensive income, statements of changes in net assets, statements of cash flows, and notes to financial statements. At the Darul Aman College Foundation, Medan City has not implemented or made financial reports in accordance with this concept. The purpose of this study is to find out how the presentation of financial statements at the Darul Aman College Foundation is in accordance with the ISAK 35 concept and to find out the benefits of financial statements that have used ISAK 35 for the Darul Aman Education Foundation.